Plasma Antioxidant Micronutrients and Oxidative Stress in People Living with HIV - Mgbekem, M.A.; John, M.E.; Umoh, I.B.; Eyong, E.U.; Ukam, N.; Omotola, B.D. (Pakistan Journal of Nutrition, 2011)
Increased lipid peroxidation induced by reactive oxygen species has been implicated in several aspects of HIV disease pathogenesis including loss of immune function, chronic weight loss, inflammatory response and decreased immune cells proliferation. The aim of this study was to evaluate plasma antioxidant micronutrients and lipid peroxidation indices in HIV positive clients (50 untreated-Not on Antiretroviral Therapy (NART), 50 on treatment with Antiretroviral Therapy-ART) and 28 sero-negative control subjects (>27 age-matched). Plasma antioxidant vitamins and lipid profile were measured. Beta-carotene levels were Control (3.44±0.46 RE), NART (5.17±0.67 RE) and ART (7.53±1.83 RE) with ART, being significantly (p<0.05) higher in ART subjects than controls. The corresponding ascorbic acid levels (mg/dl) were 1.40±0.10, 2.30±0.20 and 1.58±0.10. Levels of Superoxide Dismutase (SOD) were significantly increased in NART subjects compared with ART and controls. In contrast, the uric acid level was much lower (p<0.05) in NART subjects than ART and control groups. Malondialdehyde (MDA) was significantly higher in subjects on ART (2403.73±310.99 μ/ml) than NART (1628.11±111.56 μ/ml) and control (1459.58±119.11 μ/ml). The lipid profile showed substantially elevated levels of total cholesterol, triglyceride and Low Density Lipoprotein (LDL)-cholesterol in NART subjects compared with ART and controls. High Density Lipoprotein (HDL)-cholesterol showed no significance among the groups. Results showed increase in oxidative stress and a weakened antioxidant defense system in HIV positive persons, especially those not on antiretroviral therapy.